Sikap Dan Minat Menggunakan Mobile Banking (Studi Kasus Pada PT. Bank Pembangunan Daerah Bali Cabang Denpasar) - I Made Gede Ariestova Kurniawan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
This study aims to see the factors that influence attitudes and interests in using BPD mobile banking with attitudes as mediation. The location of the research was conducted at PT Bank Pembangunan Daerah Bali, Denpasar Branch. The population in this study were the BPD mobile banking users who were estimated to be 3,641. This research uses quantitative data types, uses primary and secondary data sources, and data analysis techniques used are interviews, documentation, and using instruments in the form of questionnaires. The sampling in this study is proportional to each customer. Meanwhile, the determination of respondents using random sampling by lottery on the customer list. The minimum number of samples to be the research target is 100 people. The analysis technique used is Structural Equation Modeling (SEM) with a variance-based or component-based approach with Partial Least Square (PLS). The results of this study indicate that: 1) Perceived benefits have a positive and significant effect on attitudes, 2) Ease has a positive and significant effect on attitudes, 3) Perceptions of benefits have a positive and significant effect on interest, 4) Ease of use has a positive and significant effect on attitudes, 5 ) Perceived benefits have a positive and significant effect on interest through attitude, 6) Ease has a positive and significant effect on interest through attitude.